Особенности и алгоритм функционального контроля природных объектов - Чурсин, А. А.; Любимова, Н. А. (НТУ "ХПИ", 2009)
Відомо, що водні джерела є біологічними системами надзвичайно складної структури. У даній статті проведений аналіз функціонального контролю природного об’єкта, запропонована математична модель, обрані й розраховані критерії якості питної води, розглянуті деякі особливості функціонального контролю природного об’єкта.

It is known, that water sources are biological systems of extremely difficult structure. In given article the analysis of the functional control of natural object is carried out, the mathematical model is offered, criteria of quality of potable water are chosen and calculated, some features of the functional control of natural object are considered.
Keywords: биологические системы; пищевые ресурсы; природные гидроэкосистемы; внутренняя среда; целостность; Фурье-преобразование